Features of maintenance of training process on the stage of higher achievements - Deminskiy, A. (8th International Sports Science Conference, Vilnius, 25-26 February 2005, 2005)
Zur Bedeutung des langfristigen Leistungsaufbaus zur Optimierung der Möglichkeiten des Athleten in der Etappe des Hochleistungstrainings - nach bereits langjährigem Training.